Lightweight security against combined IE and SSDF attacks in cooperative spectrum sensing for cognitive radio networks. Issue 18 (22nd July 2015) - Sucasas, Victor; Althunibat, Saud; Radwan, Ayman; Marques, Hugo; Rodriguez, Jonathan; Vahid, Seiamak; Tafazolli, Rahim; Granelli, Fabrizio
Abstract: Cognitive radio is envisaged as a promising solution to cope with the problem of spectrum scarcity. In cognitive radio networks, users can sense the medium and opportunistically use available frequency bands. Users can cooperate in order to increase the reliability of the sensing process, which is called cooperative spectrum sensing (CSS). However, cooperative paradigms are threatened by the behavior of malicious users. Two types of attacks represent the main threats for CSS network operation, namely, spectrum sensing data falsification (SSDF) and incumbent emulation (IE). These two types of attacks have received a considerable amount of attention in the literature, but they have always been studied separately. In this paper, we propose a novel mechanism based on lightweight cryptography that considers both SSDF and IE attacks combined in a CSS network for the first time. Lightweight cryptography, in contrast to previous techniques used (such as intrusion detection or reputation systems), provides higher resilience to such attacks when a high number of mobile malicious users exist, providing better energy efficiency. Analytical and simulation results show the outperformance of the proposed algorithm compared with previous mechanisms, in terms of lower false alarm probability (i.e., higher chance of using the free frequency bands) and hence better energy ratings. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : This research work proposes lightweight cryptography to address a scenario with combined spectrum sensing data falsification and incumbent emulation attacks. The proposed security protocol uses message‐authenticated codes with variable length in order to optimize the energy efficiency trade‐off. Simulation and analytical results show clear gains in terms of false alarm probability and energy efficiency.